Estimation of habitual iodine intake in Japanese adults using 16 d diet records over four seasons with a newly developed food composition database for iodine. Issue 4 (22nd July 2015) - Katagiri, Ryoko; Asakura, Keiko; Sasaki, Satoshi; Hirota, Naoko; Notsu, Akiko; Miura, Ayako; Todoriki, Hidemi; Fukui, Mitsuru; Date, Chigusa
Abstract : Although habitual seaweed consumption in Japan would suggest that iodine intake in Japanese is exceptionally high, intake data from diet records are limited. In the present study, we developed a composition database of iodine and estimated the habitual intake of iodine among Japanese adults. Missing values for iodine content in the existing composition table were imputed based on established criteria. 16 d diet records (4 d over four seasons) from adults (120 women aged 30–69 years and 120 men aged 30–76 years) living in Japan were collected, and iodine intake was estimated. Habitual intake was estimated with the Best-power method. Totally, 995 food items were imputed. The distribution of iodine intake in 24 h was highly skewed, and approximately 55 % of 24 h values were < 300 μg/d. The median iodine intake in 24 h was 229 μg/d for women and 273 μg/d for men. All subjects consumed iodine-rich foods (kelp or soup stock) on one or more days of the sixteen survey days. The mean (median) habitual iodine intake was 1414 (857) μg/d for women and 1572 (1031) μg/d for men. Older participants had higher intake than younger participants. The major contributors to iodine intake were kelp (60 %) and soup stock (30 %). Habitual iodine intake among Japanese was sufficient or higher than the tolerable upper intake level, particularly in older generations. The association between high iodine intake as that observed in the present study and thyroid disease requires further study.